The effectiveness of environmental education workshops for teachers, learners and schools in Malaysia - Loubser, Callie; Noor Azlin, Yahya; Dreyer, Johann; Nik Azyyati, Abdul Kadir (Environment, development and sustainability, 2014)
In Malaysia, various efforts have been introduced to increase the knowledge, skills and awareness of citizens to the benefit of the environment by means of a variety of programmes. However, uncertainty about the effectiveness of environmental education programmes and the way they contribute to sustainability still exists. This paper reports on an evaluation of the Kelab Pencinta Alam (KPA) (School Nature Clubs) programme organised by the Malaysia Nature Society and the Forest Research Institute of Malaysia. The Kellogg Logic Model was used as an evaluative instrument as the impact of the programme had to be determined. This was done through questionnaires to teachers and principals in KPA schools. School visits were also undertaken to evaluate workplace success and to validate the findings from the questionnaires. Overall, the evaluation showed a high level of success for the programme.